Galen and the Stoic ‘Double Perversion’ Theory - Boeri, Marcelo D. (ΠΗΓΗ/FONS, 2020)
Galen argues that the Stoic view that children are immediately familiar with what is good is false. Chrysippus holds that when a person acts badly, this is so because her nature has been perverted, and that the cause of perversion (διαστροφή) is twofold: the influence of the companions and what derives «from the very nature of things». Children, Galen contends, rush towards pleasure and avoid pain without any instruction. Additionally, they become angry, which proves that the first natural thing is not a propensity to what is good, but to emotions. However, Galen grants that, although at the beginning children are familiar with pleasure and victory, when they grow up, they have a natural familiarization with the good. In this paper I argue that the Stoics have a reasonable way of replying to Galen’s objection: since he admits that when human beings develop their rationality, a familiarization with the good comes about (such familiarization to the good being something natural), he implicitly grants that the inclination to the good is part of human nature. In my discussion I briefly deal with the first orientation of the human animal towards himself, and suggest that this is the first good; in fact, for animals the appropriate thing to do is to pursue the primary natural goods that guarantee the preservation of their own constitution. That initial good is not yet a moral good, but it is a necessary condition for the correct development of the person, which will foster the correct development of one’s inclination towards what is appropriate in a moral sense.
Keywords: Galen; stoics; perversion; natural good; human animal; ethics